Climeto-Cylic Immigrations with Declining Population of Wild Honeybee, Apis Dorsata F. In Chitwan Valley, Nepal - Pokhrel, Saroj (Journal of Agriculture and Environment, 2010)
A general survey was conducted to investigate the phenomena of seasonal immigration, aggregation and staying of Apis dorsata Fab. colonies in Chitwan valley, Nepal in 2003/04. The primary immigration of small colonies occurred during November-December in Southern areas and secondary type mainly from site shifting of the large colonies towards north of Chitwan valley in January-February and smaller colonies through swarming in March-April respectively. Maximum colonies aggregated in March with maximum staying of eight months. Colonies aggregation declined by 54%, 50% and 100% in May, June and July and the period of colony staying declined by 25% as compared to previous years. The causes of population decline were: bad weather, predators and parasites, honey hunting, increasing pesticide use, declining bee pasture and inter species competition with exotic A. mellifera L. Policy declaration with suitable programs for the conservation of native wild honeybee, A. dorsata in its indigenous habitat for the maintenance of biodiversity and raising the crop productivity is necessary. Key words: Aggregation; Bee pasture; Biodiversity; Colony staying; Honey hunting; Immigration; Nesting site; Swarming The Journal of AGRICULTURE AND ENVIRONMENT Vol. 11, 2010 Page: 51-58 Uploaded Date: 15 September, 2010